2014
DOI: 10.1071/bt14102
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress differently affects growth, water status and antioxidant enzyme activities in Solanum lycopersicum and its wild relative Solanum chilense

Abstract: The effect of saline stress (NaCl, 40, 80 and 160 mmol L−1 of NaCl) on growth, plant water status and leaf antioxidant enzyme activities was investigated in a commercial cultivar of cherry tomato (Solanum lycopersicum var. cerasiforme L.) and in a wild-related species collected in a salt-affected area of North Chile (Solanum chilense Dun.). Salt stress was applied in a nutrient solution at the vegetative stage during 40 days. The highest NaCl concentration reduced shoot relative growth, fresh and dry weight an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Comparing the behavior of the cultivated glycophyte S. lycopersicum with its wild‐relative halophyte plant species S. chilense will help to unravel the strategies of plant response to salt stress and may also lead to identification of genes able to confer salt resistance to the cultivated tomato. Martínez et al (, ) reported that S. chilense displays a contrasting behavior in response to prolonged exposure to moderate salinity compared with S. lycopersicum and that salt stress does not markedly affect plant biomass and fruit yield in this species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the behavior of the cultivated glycophyte S. lycopersicum with its wild‐relative halophyte plant species S. chilense will help to unravel the strategies of plant response to salt stress and may also lead to identification of genes able to confer salt resistance to the cultivated tomato. Martínez et al (, ) reported that S. chilense displays a contrasting behavior in response to prolonged exposure to moderate salinity compared with S. lycopersicum and that salt stress does not markedly affect plant biomass and fruit yield in this species.…”
Section: Introductionmentioning
confidence: 99%
“…This species can dwell in hyper arid areas and is distributed from sea level up to 3500 m in the Andes (Chetelat et al ). This self‐incompatible perennial was historically included in the polymorphic Solanum peruvianum but is now considered as a distinct species found in a geographically restricted area and characterized by narrow ecological niches (Igic et al , Nakazato et al , Tellier et al ).This wild tomato species is able to grow in diverse environments and to cope with many biotic and abiotic constraints (Martínez et al , ). It is commonly considered as a valuable source of genes for resistance to viruses such as Pseudomonas syringae (Thapa et al ) or tomato yellow leaf curl disease (Pérez de Castro et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Osmotic adjustment during salt stress in S. lycopersicum might result in the turgor loss point occupying at lower leaf water potential ( Suárez, 2011 ). Martínez et al (2014) reported that higher water-retaining ability on leaf dry weight basis during salt stress condition is an important tolerance strategy and could be correlated with higher stress tolerance in S. chilense than S. lycopersicum .…”
Section: Discussionmentioning
confidence: 99%
“…It has extreme potential to grow well in diverse and fluctuating environments. The tolerance of this wild species to such harsh environment is possibly due to presence of essential genes that govern key tolerance traits against various abiotic and biotic stresses ( Martínez et al, 2014 , Thapa et al, 2015 ). Interestingly, biochemical and physiological basis of salt resistance in S. chilense has been less explored when compared to other wild relatives such as Solanum cheesmanii , Solanum pennellii , and Solanum pimpinellifolium ( Almeida et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main reasons for these conflicting results may relate to the genetic background of the assessed tomato cultivars, which holds varying salt tolerances [ 48 ]. Indeed, various key mechanisms within the plant stress response have been recognized to be universal, but their relative importance may vary from species to species, depending amongst other on the metabolic background [ 49 ]. This statement has clearly been demonstrated in the study of Caro et al (1991) [ 50 ] in which normal-fruited tomato cultivars ( Solanum lycopersicum L.) were found to be less salt tolerant compared to cherry tomatoes ( Solanum lycopersicum L. var.…”
Section: Discussionmentioning
confidence: 99%